Science related activities within sociocultural community development interventions can be just entertaining? - Teodoro, Ana (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales)

(untitled) (Département de communication sociale et publique, Université du Québec à Montréal, 2014)
Science and technology are increasingly present on contemporary societies and the ideological requirement of informed democratic citizenship implies the need that individuals learn and understand science. It is both a cultural object and product that can be received and worked at different levels and within several approaches by the individuals and the communities. Part of this work can be addressed by the professionals of sociocultural community development. A set of fields of action is available for the intervention of these workers, therefore giving to these professionals an important part in conquering, with and within the communities, a democratic space where more informed citizens can improve democratic participation. In this text, the options taken by students when designing science related activities within the context of an optional course of a 1st cycle of a portuguese program over the past four years are analysed and discussed. Entertaining activities seem to be a quite common choice among these students.